Maxillary Sinus Lift Using Autologous Periosteal Micrografts: A New Regenerative Approach and a Case Report of a 3-Year Follow-Up - Saturnino Marco Lupi; Arianna Rodriguez y Baena; Claudia Todaro; Gabriele Ceccarelli; Ruggero Rodriguez y Baena (Hindawi Limited, 2018)
This case report discusses about an innovative bone regeneration method that involves the use of autologous periosteal micrografts, which were used for a maxillary sinus floor lift in a 52-year-old female patient. This method allows for harvesting of a graft that is to be seeded on a PLGA scaffold and involves collection of a very little amount of palatal periosteal tissue in the same surgical site after elevation of a flap and disaggregation of it by using a Rigenera® filter. Histological samples collected at the time of implant installation demonstrate a good degree of bone regeneration. The clinical and radiographic outcomes at the 3-year follow-up visit showed an adequate stability of hard and soft tissues around the implants. This report demonstrates the possibility to obtain a sufficient quality and quantity of bone with a progenitor cell-based micrograft and in turn make the site appropriate for an implant-supported rehabilitation procedure, with stable results over a period of two years.